2014
DOI: 10.1155/2014/141627
|View full text |Cite
|
Sign up to set email alerts
|

Ethical, Socioeconomic, and Cultural Considerations in Gynecologic Cancer Care in Developing Countries

Abstract: Gynaecologic cancers contribute significantly to the cancer burden in developing countries, resulting in higher mortality and morbidity rates among women in these nations. This situation is further compounded by the occurrence of wars, famine, poverty and natural disasters, and infectious diseases like hepatitis B and HIV/AIDS. In addition, merge resources and manpower lack in these countries further compound this very delicate situation. Often times, socioeconomic, cultural, and ethical factors such as truth-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 43 publications
3
17
0
Order By: Relevance
“…Results also showed that cervical cancer is predominant in the younger age groups (40-49 years). For cervical cancer, the main histological type of cancer was squamous cell carcinoma, which is similar to a study performed in Nigeria in which squamous cell carcinoma was predominant (92%) (24).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Results also showed that cervical cancer is predominant in the younger age groups (40-49 years). For cervical cancer, the main histological type of cancer was squamous cell carcinoma, which is similar to a study performed in Nigeria in which squamous cell carcinoma was predominant (92%) (24).…”
Section: Discussionsupporting
confidence: 84%
“…Late stage diagnosis requires long, complex, very aggressive and costly treatment; thus, the management of ovarian cancer in developing countries poses a great challenge (24).…”
Section: Discussionmentioning
confidence: 99%
“…Socioeconomic and cultural factors often lead to late presentation and diagnosis, more mortality, and poor follow-up of cancer survivors. The above countries/societies are known to have rich and diverse cultures where religions, traditions, and family values greatly infl uence medical decision [14].…”
Section: Factors Interfering With Cancer Carementioning
confidence: 99%
“…Among the ethical challenges are issues like: individuals' autonomy, family and community participation in care, and end-of-life issues. For the successful development of a viable and sustainable model of cancer care in resource-poor environments, these issues must be dealt with [14].…”
Section: Factors Interfering With Cancer Carementioning
confidence: 99%
“…10 in the developing countries, fear of cancer, lack of resources and lack of effective knowledge in avoiding screening for cancer are involved. 11 The obstacles in Iran are factors such as fear of pain during mammography and its complications, high costs, lack of physician recommendation on mammography, 12 the diagnosis of a serious illness and fear of rejection by their husbands, family members, and friends. In addition, Iran's religious background was involved in this attitude so that belief in fate and the will of God lead to their reluctance to do preventive measures.…”
Section: First Stagementioning
confidence: 99%